Contesting masculinity between Robin Hood and Azeem As Seen In Robin Hood : Prince of Thieves ( 1991 ) - Erika Estinia Oktaviyani (Fak. Adab dan Ilmu Budaya Universitas Islam Negeri, 2022)
et,1/adil,c.1